Facile Fabrication and Microstructure of α‐Al2O3/TiC Composite Coating as Tritium Permeation Barrier. (8th April 2015) - Lu, Caixuan; Li, Heping; Liu, Xiaobang; Xue, Lihong; Yan, Youwei
Abstract : Well‐crystallized α‐Al2 O3 /TiC composite coating was synthesized on the surface of steel substrate by a facile laser‐assisted combustion synthesis technique without subsequent calcination. The effect of laser cladding speed on formation and microstructure of the coatings was studied. At 6 mm/s, α‐Al2 O3 /TiC coating with good quality was obtained without pores and cracks and was well bonded with the steel substrate. By adjusting the precoating thickness, the coating thickness was easily controlled. As a simple, environmentally friendly and energy‐saving technique, laser‐assisted combustion synthesis is expected to find applications in ceramic coating fabrication as tritium permeation barrier or wear‐ and corrosion‐resistance coatings.